PKM PELATIHAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA DAN PEMASARAN ONLINE KELOMPOK USAHA PENGRAJIN TENUN DI BALI - I Gusti Ayu Ratih Permata Dewi; Putu Yudha Asteria Putri; Putu Gede Wahyu Satya Nugraha (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
The Ngaben ceremony is a cremation tradition in Balinese culture, Indonesia. The weaving used in this ceremony has special meaning and symbolism. The selection of weaving for the Ngaben ceremony is generally adjusted to local beliefs and traditions. Several types of weaving that are generally used in the Ngaben ceremony involve certain colors and motifs that have deep meaning. From the raw material, yarn will become woven fabric. Weaving craftsmen in Kumbasari Market, Denpasar City, Bali can produce various kinds of woven fabrics for the Ngaben ceremony. The community service program is carried out in the trading and production business of weaving crafts "Tenun Lestari" located in Denpasar City, Bali Province. Tenun Lestari is a partner owned by I Made Mertadana as well as a maker/craftsman of weaving crafts. The problems faced by partners include: 1) Not having bookkeeping to calculate business profits and losses. 2) Not having bookkeeping in calculating the cost of production. 3) Not having a product brochure so it is difficult to do promotions. The solutions offered to overcome these problems include: 1) Establishment and design of a profit and loss bookkeeping system, 2) Establishment and design of a production cost bookkeeping system, and 3) Making brochures of the products owned.